Mucoepidermoid carcinoma of salivary glands: A French Network of Rare Head and Neck Tumors (REFCOR) prospective study of 292 cases. Issue 6 (June 2021) - Dahan, Laurie Saloner; Giorgi, Roch; Vergez, Sébastien; Le Taillandier de Gabory, Ludovic; Costes-Martineau, Valérie; Herman, Philippe; Poissonnet, Gilles; Mauvais, Olivier; Malard, Olivier; Garrel, Renaud; Uro-Coste, Emmanuelle; Barry, Béatrix; et al.
Abstract: Background: To describe the characteristics of the largest European study of MEC of salivary glands and to determine the prognostic factors for overall and disease free survival. Patients and methods: Patients with MEC were prospectively included in the Réseau d'Expertise Français sur les Cancers ORL Rares (REFCOR, French Network of Rare Head and Neck Tumors) database between 2009 and 2015. Results: A total of 292 patients were included. Tumors were classified as low grade in 175 cases (60%), intermediate in 39 (13%) and high grade in 78 (27%). Median follow-up was 26 months. The 5-year OS and DFS rates were respectively 83% and 69%. In multivariate analysis, age (p = 0.004), diabetes (p = 0.02) and advanced stage (p = 0.03) were found to have a significant negative impact on OS. Diabetes (p = 0.001), alcohol consumption (p = 0.003) and advanced stage (p = 0.001) were found to have a significant negative impact on DFS. Compare to low grade, high grade tended to have a negative impact on OS (p = 0.05) and had a significant effect on DFS (0.002) while intermediate grade had no significant influence on survival. The surgical treatment had a positive impact on both OS (p = 0.00005) and DFS (p = 0.0005). Postoperative radiotherapy had no impact in multivariate analysis. Conclusion: Advanced clinical stage, high grade tumor, high age, the impossibility of carrying out a complete surgical resection, and diabetes are the main prognostic factors in this prospective series of patients with MEC. Such findings open new research perspectives on the influence of these components on initial patient care.